G162 Adolescents and their parents' experiences of internet delivered home treatment for chronic fatigue syndrome/me (fitnet-NHS trial). (25th October 2020) - Parslow, RM; Anderson, E; Brigden, A; Rai, M; Mills, N; Crawley, E
Abstract : Aims: We aimed to understand the acceptability of two internet-delivered home treatments for paediatric Chronic Fatigue Syndrome/Myalgic Encephalomyelitis (CFS/ME) as part of the FITNET-NHS randomised controlled trial. The two interventions were: i) an online Cognitive Behavioural Therapy (CBT) programme (FITNET-NHS) supported by therapist e-consultations; ii) Activity Management delivered by clinicians via Skype. Methods: In-depth qualitative interviews were undertaken with families taking part in the FITNET-NHS Trial to understand the acceptability of receiving treatment at home via the internet. Participants were purposively selected for maximum variation (intervention, age and gender). Interviews followed a checklist of topics. All interviews were audio-recorded, transcribed verbatim, uploaded to NVivo and analysed using thematic analysis. Results: Interviews were undertaken with 29 families (15 FITNET-NHS arm; 14 Activity Management arm). This included 26 young people (15 females and 11 males, ranging from 12–17 years old) and 31 parents (27 mothers and 4 fathers). Four key themes and 9 sub themes emerged. Participants talked about the 1) benefits of online treatment including: no need to travel reducing payback, ease of use, convenience and flexibility as well we the ability to revisit online content for clarity and motivation. The 2) disadvantages of online treatment included: technical problems, difficulty building a rapport and feeling unable to communicate effectively online and preferring to see the therapist in person. Participants felt 3) Contact with a therapist is essential to give parent support and backing and provide specialist knowledge and tailored advice. The final theme highlighted how 4) the digital interventions need to be tailored according to: age, severity and communication preference differences. Conclusion: Young people and their parents discussed the benefits and disadvantages of online treatment for CFS/ME. Whilst some feel it is as good as face to face contact, others found it difficult to communicate through emails and Skype and would have preferred to see a therapist in person. Therapist contact is viewed as essential to provide specialist knowledge and support. Internet-delivered interventions for paediatric CFS/ME need to be tailored to take into account individual differences such as age, severity and communication preferences.